Cover Feature: Reconstruction of Copper Nanoparticles at Electrochemical CO2 Reduction Reaction Conditions Occurs via Two‐step Dissolution/Redeposition Mechanism (ChemElectroChem 14/2021). Issue 14 (17th June 2021) - Popovic, Stefan; Bele, Marjan; Hodnik, Nejc
Abstract : The Cover Feature illustrates the reconstruction of electrodeposited copper nanoparticles (ED CuNPs) at the relevant CO2 electroreduction conditions. Identical location scanning electron microscopy (IL‐SEM) as the main method enabling tracking of the stability of the individual ED CuNPs we reveal that Cu reconstruction occurs via a two‐step dissolution/redeposition mechanism. More information can be found in the Article by S. Popovic et al .